Biological Effects of HIFU on HT-29 Colon Cancer Cell Lines - (:unkn) unknown (IEEE, 2018)
In this study, biological effects of High Intensity Focused Ultrasound (HIFU), which offer an effective treatment options for the treatment of solid tumors in recent years, will be determined on the colon cancer cell lines.
Keywords: HIFU; colon cancer; cancer treatment; apoptosis; cancer cell lines; HEAT-INDUCED APOPTOSIS